METODE PENYELESAIAN HADIS-HADIS MUKHTALIF OLEH SYEKH SALIH AL-‘USAIMIN - Ardianti, Siti (UIN Sumatera Utara Medan, 2019)
Some problems revolve around the Hadith from quality problems to erroneous and misleading understandings. Other problems are a number of contradictory traditions in physical terms. This Hadith may not be practiced unless it has been ascertained that the hadith is free from opposition and is free from cancellation. The process of ascertaining the element of ikhtilaf in the hadith to find a way to resolve it properly cannot be solved by just anyone except a handful of ulama who are experts in the fields of hadith, fiqh and ushul fiqh. One of the contemporary scholars who was considered qualified in this field was Sheikh Salih al-Usaimin. So this paper aims to find out how to solve the Hadith Mukhtalif Sheikh Usaimin. By using a character study approach through tracing the works and thinking in the field of Hadith and others. The results of the study indicate that the completion of Sheikh Usaimin's authentic traditions is using the plural method, nasakh, tarjih and tawaqquf. But as far as the author's research on the tawaqquf method, Sheikh Usaimin did not give an example of his case, as strengthened by his own statement in his book al-Usul min ‘Ilmi al-Usul, which explains that there is no right example for the tawaqquf method. Through this article, it is hoped that we can appear as nashir as-sunnah by examining the problems of hadith and developing theories of Hadith science that have been passed down by previous scholars.